Mycotoxin patulin contamination in various fruits and estimating its dietary impact on the consumers: from orchard to table - Iqbal, Shahzad Z.; Waseem, Muhammad; Abdull Razis, Ahmad Faizal; Bhatti, Ijaz A.; Khaneghah, Amin Mousavi; Mohammed, Osama A.; Lakshminarayanan, Srimathi Priya; Iqbal, Munawar (Elsevier, 2024)
The present research examined patulin's presence across the whole supply chain of selected fruits. A comprehensive analysis was conducted on 442 samples of fruits (oranges, apples, apricots, lemons, and guava) to determine the presence of patulin contamination. This analysis used Liquid Chromatography (HPLC) with a UV detector. The findings indicate that 17, 23, and 28 % of selected fruit samples tested positive for patulin levels in farm, transportation, and market samples. However, the sample collected during the transportation step showed that 56 % (percentage of positive samples) of fruits have patulin levels greater than 50 μg/kg, and 41 % (percentage of positive samples) have greater levels than 50 μg/kg in market samples. The findings of the one-way analysis of variance indicated that no statistically significant variation existed between the amounts of patulin across the various stages of the food supply chain system (p > 0.05). Nevertheless, the analysis of the correlation study, namely Kendall's tau_b and Spearman's rho, denote a robust association between the levels of patulin and the food supply system. The apple samples exhibited the most significant average dietary intake of patulin, with an average value of 0.11 μg/kg bw/day. The maximum mean hazard quotient (HQ) of 0.28 was also recorded. The prevalence and incidence of patulin in specific fruits were found to be relatively high, and it was observed that market samples had elevated levels of patulin in the selected fruits.